Tinjauan Sistematis tentang Pencetakan Makanan 3D: Perkembangan dari Konsep Menjadi Realita: A Systematic Review on 3D Food Printing: Progressing from Concept to Reality - Manivelkumar, Koushikha Namakkal; Kalpana, Chinnappan A (Amerta Nutrition, 2025)
Background: Using 3D printing technology, novel items can be created from various materials, including edible ones, addressing the growing importance of sustainable food chains and personalized nutrition. As the latest advancement in additive manufacturing, 3D printing meets diverse customer demands by producing customized food items tailored to individual nutritional needs. Objectives: This literature evaluation focuses on the applications, technical advancements, and future possibilities of 3D food printing. By assessing recent developments, the study explores its adaptability and transformative potential in addressing global issues such as sustainability and personalized nutrition. Methods: To include up-to-date and relevant data, PubMed, Google Scholar, and Scopus were searched for research on "3D Food Printing," "Food Technology," "Food Formulation," and "Customized Diet" from 2018 to 2024. Data extraction and synthesis were conducted on 31 reports selected from 687 search results after removing duplicates and applying filters. Discussions: The study highlights the use of 3D food printers for creating dairy products, fish and meat, pasta, biscuits, chocolates, and cereal-based foods. Applications span industries such as space food, elderly and school children's nutrition, military food, hospitals, and restaurants. Future research directions include food characterization through color analysis, moisture content, water activity, physiochemical properties, and microbiological studies. Conclusions: This study highlights the potential advantages of 3D food printing technology, including healthier food options, novel dining experiences, and diet customization. It underscores its transformative capacity to impact the global economy while addressing sustainability and personalized nutrition challenges.